Analisis Penerapan Etika Bisnis Islam Pada Produk UMKM Tahu di Desa Duren Kota Madiun - Irawati, Dyan (Transformasi: Journal of Economics and Business Management, 2024)
This study aims to analyze the application of Islamic business ethics to the UMKM tofu products in Desa Duren, Kota Madiun. Desa Duren is known for its tofu production, which is one of the main sources of income for the local community. This study uses a qualitative approach with a case study method to explore how the principles of Islamic business ethics are applied in the production and distribution processes of tofu. Data were collected through in-depth interviews with UMKM actors, field observations, and documentation studies. The results show that the application of Islamic business ethics, such as honesty, justice, responsibility, and concern for community welfare, has had a positive impact on the sustainability of the business and the economic well-being of the Desa Duren community. Additionally, the application of these ethics has also enhanced the reputation and consumer trust in the tofu products. This study concludes that the application of Islamic business ethics is not only relevant but also essential in creating an environment of integrity and sustainable business practices. The study's recommendations include increasing education and training for UMKM actors about Islamic business ethics and support from the government and related institutions to strengthen ethical and sustainable business practices. This research contributes to the development of knowledge in the field of Islamic business ethics and the economic empowerment of the local community.